THE EFFECT OF VITAMIN A TREATMENT ON RENAL GLOMERULAR AREA OF RATS MODEL DIABETES MELLITUS TYPE 2 - Pratiwi, Made Dinda; Adi, Prasetyo; Anita, Kenty Wantri (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background: Diabetes mellitus (DM) type 2 is a metabolic disorder due to defects in insulin secretion. A microangiopathy complication of DM in the kidney can lead to renal enlargement. This augmentation in renal size can be attributed to several factors, including glomerular hypertrophy, tubular hypertrophy, and interstitial expansion. Retinoic acid, a vitamin A derivative, serves numerous cellular roles, including the induction of cell differentiation, the regulation of apoptosis, and exhibiting anti-inflammatory and antifibrotic properties.Objective: This study aims to evaluate the effect of vitamin A administration on the renal glomerular area in a rat model of type 2 diabetes mellitus. Methods: This study was experimental with five groups, including a negative control group, a positive diabetes mellitus group, and three groups of vitamin A treatment. The primary variable assessed was the glomerulus area across the different groups.Results: No significant decrease in glomerular area was observed in the vitamin A treatment group within the positive diabetes (ANOVA, p = 0.052).Conclusions: The findings of this study suggest that the administration of vitamin A does not significantly affect the reduction of renal glomerular area in rats with diabetes mellitus.